Steatorrhoea in Acute Enteritis - A. H. Sutanto; Rahayu Sa'at; H. Siregar (Indonesian Pediatric Society, 1982)
Out of a total of 678 patiems, 190 infants presenting acute en1eritis. 95.7%were below 2 yeaÂ·s of age and 86.8% were below 1 year of age. Fat dropletswere found in 25 out of 143 patients (17,4%) below 12 months of age.Sugar intolerance was found in 39 of 86 infollts examined (45,3%). Thehighest prevalence was in the a,;P group of 6- 9 11101:ths.The prevalence of concomitant intestinal parasites was low.